APPLIED RESEARCH AND DEVELOPMENT IN COOPERATION WITH INDUSTRY - Ermolayev, B.A.; Tatarintseva, O.C. (Journal of Information Technologies in Education (ITE), 2010)
Cooperation with the industrial enterprises today becomes a much more attractive way of guaranteing the advancement of the basic and applied research and development at the Universities. Besides the industrial partners are an important source of new scientific ideas and up-to-date industrial technologies in their industrial branches. Successful cooperation with industrial partners allows the universities not only to improve their advancement in the respective research fields but also to raise the quality of and the industrial demand for their own product: new technologies and individuals qualified for knowledge work. The paper presents the five year experience and the major outcomes of the cooperation of a research group at Zaporizhzha National University with their European industrial partners using three different projects as examples.